SELF-EFFICACY MEDIATES THE RELATIONSHIP BETWEEN SEXUAL EDUCATION AND PREVENTION OF SEXUALLY-TRANSMITTED DISEASES AWARENESS AMONG SECONDARY SCHOOL STUDENTS IN PADANG CITY, INDONESIA - NINDREA, Ricvan Dana; DARMA, Ika Yulia (African Journal of Infectious Diseases (AJID), 2024)
Background: Adolescence is a crucial stage for developing behaviors that impact long-term sexual and reproductive health, particularly in LMICs like Indonesia. This study examined the relationship between sexual education, self-efficacy, and awareness of sexually transmitted diseases (STDs) prevention among secondary school students in Padang City, Indonesia. Materials and Methods: A cross-sectional study was conducted with 254 students aged 12-15 years, using self-administered questionnaires and a multi-stage stratified cluster sampling technique. Data analysis was performed using Structural Equation Modelling (SEM). Results: SEM revealed significant relationships between self-efficacy and STDs prevention (β=0.528, P<0.001), self-efficacy and sexual education (β=0.220, P=0.001), and sexual education and STDs prevention (β=0.218, P=0.001). Conclusion: These findings highlight the importance of self-efficacy as a mediator in enhancing the effectiveness of sexual education programs, suggesting that boosting students’ confidence in their ability to protect themselves can improve STDs prevention behaviors.